PENGARUH PERCEIVED VALUE DAN E-SERVICE QUALITY TERHADAP SWITCHING COST DAN CUSTOMER LOYALTY - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2017)
The purpose of this study was to determine the effect of perceived value and e-service quality on switching costs and customer loyalty. The sample of this study is Tokopedia users who have made at least 1 transaction in the past month in Kebumen totaling 100 respondents. The sampling technique uses nonprobability sampling technique, namely purposive sampling. Methods of data collection using questionnaires, literature studies and interviews. Analysis of the data used is the instrument validity and reliability test, the classic assumption test, hypothesis testing and path analysis using the SPSS 22 program for windows. The results of this study indicate that all items of each variable are valid and reliable. Both structural models meet the classic assumption test criteria with no multicollinearity, heterokedasticity, and normality assumptions. Based on the results of the t test showed that the variable perceived value and e-service quality significantly influence the switching cost, perceived value does not affect customer loyalty, e-service quality has a significant effect on customer loyalty, switching cost has a significant effect on customer loyalty.